1988
DOI: 10.1111/j.1365-2621.1988.tb00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of food‐borne pathogens by lactic and acetic acids and their mixtures

Abstract: The inhibition of Salmonella enteritidis and E. coli by lactic and acetic acids, individually and as equimolar mixtures, was measured. Results confirm that the undissociated acid is the active antimicrobial species. In weakly buffered media an apparently synergistic interaction is observed between the two acids; this is ascribed to the potentiation of acetic acid in the lower pH environment created by the lactic acid. The effect could account for the stability of vegetable fermentations where no starter cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0
8

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(79 citation statements)
references
References 5 publications
3
68
0
8
Order By: Relevance
“…According to Wong and Chen (1988), the inhibitory effect of acetic acid is the highest from among all of the organic acids. The inhibitory effect of both acids mentioned increases with decreasing pH and a synergistic effect of lactic and acetic acid on E. coli and Salmonella enteritidis becomes apparent (Adams and Hall, 1988). Lactic acid decreases the pH of the medium, which results in an increased toxicity of acetic acid.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wong and Chen (1988), the inhibitory effect of acetic acid is the highest from among all of the organic acids. The inhibitory effect of both acids mentioned increases with decreasing pH and a synergistic effect of lactic and acetic acid on E. coli and Salmonella enteritidis becomes apparent (Adams and Hall, 1988). Lactic acid decreases the pH of the medium, which results in an increased toxicity of acetic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inhibitory eVect on microorganism of organic acids has been widely reported to be caused by their undissociated form [7,8]. Finally, the enzymatic activity and the chemical alterations are also inXuenced by the acidity.…”
Section: Introductionmentioning
confidence: 99%
“…During fermentation, the growths of pathogens as well as other spoilage organisms are frequently inhibited through antimicrobial components produced by lactic acid bacteria (LAB) (5)(6)(7). Reports have shown that LAB-produced organic acids can work in combination to display a strong inhibitory activity against many foodborne pathogens such as Salmonella typhimurium, Escherichia coli, Bacillus cereus, Clostridium botulinum, C. perfringens, Listeria monocytogenes, and Staphylococcus aureus (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%